Research of the Mode Instability Threshold in High Power Double Cladding Yb‐doped Fiber Amplifiers. Issue 8 (3rd July 2017) - Wang, Yanshan; Liu, Qinyong; Ma, Yi; Sun, Yinhong; Peng, Wanjing; Ke, Weiwei; Wang, Xiaojun; Tang, Chun
Abstract : The double cladding Yb‐doped fiber amplifier experiment shows a mode instability (MI) behavior which depends on the pump linewidth. The amplifier with different linewidth laser diodes pumping and different cooling efficiency of gain fiber, also an evaluation method of MI threshold was proposed in this paper. Both experiments and theoretical calculations reveal the local property of the MI behavior. Abstract : We experimentally investigate the behavior of the mode instability (MI) threshold in the double cladding Yb‐doped fiber amplifier when the amplifier is pumped by broad linewidth laser diodes and narrow linewidth laser diodes respectively. It is found that the MI threshold increases by 26% when the amplifier is pumped by the broad linewidth laser diodes. Experiment results show that the MI threshold is affected by the local heat load rather than the average or the total heat load. The calculation shows that the local heat deposit actually plays the key role to stimulate the MI behaviour. At the MI threshold position in the fiber, the local heat deposit also changes dramatically. The effect of the thermal conductivity on the MI threshold is also studied. Our investigation shows that the MI threshold increases from 1269 W to 1950 W when the thermal conductivity of the fiber amplifier is increased from 0.3  W / ( m · K ) to 5  W / ( m · K ) . Through optimizing the pump linewidth and the cooling efficiency of the gain fiber, the MI threshold is doubled in our experiment.